Phylogenetic relationships between pinworms (Nematoda: Enterobiinae) parasitising the critically endangered orang-utan, according to the characterisation of molecular genomic and mitochondrial markers - Foitová, Ivona; Civáňová, Kristína; Baruš, Vlastimil; Nurcahyo, Wisnu (Parasitology research, 2014)
Pinworms (Nematoda: Enterobiinae) include 52 species parasitising primates throughout the world. In the present study, we performed the first ever molecular analysis to investigate the phylogenetic position of recently described pinworms parasitising the Sumatran orang-utan. The phylogenetic analysis of mitochondrial CO1 and chromosomal 18S rDNA and ITS1 regions could support the independent status of several Nematoda species. Our molecular data clearly suggest that Enterobius (Colobenterobius) buckleyi and Lemuricola (Protenterobius) pongoi together with Pongobius hugoti form separate clades among other studied species, which significantly supports the hypothesis of recently described new species parasitising the orang-utan (Pongo abelii and Pongo pygmaeus). The phylogenetic tree based on cytochrome oxidase 1 (CO1) gene variability showed possible close relationships between L. (Protenterobius) pongoi and P. hugoti; thus, we can assume that these species could have initially diverged in sympatry from a common ancestor.
Keywords: Mitochondria; vznik druhů (genetika); Phylogeny; enterobióza; DNA, Intergenic; Molecular Sequence Data; genetické markery; molekulární sekvence - údaje; Enterobiasis; mitochondrie; Enterobius; zvířata; Amino Acid Sequence; respirační komplex IV; Pongo abelii; fylogeneze; Genetic Markers; Genetic Speciation; Pongo pygmaeus; Electron Transport Complex IV; Animals; intergenová DNA; sekvence aminokyselin